2006
DOI: 10.1177/147323000603400509
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4, Interleukin-8 and E-selectin Levels in Intranasal Polyposis Patients with and without Allergy: A Comparative Study

Abstract: Intranasal polyposis is a chronic inflammatory upper airway disease with unknown aetiology. Interleukin (IL)-4 and IL-8 play very significant roles in allergic events and infectious inflammation, respectively. In contrast, E-selectin is important in the initiation and organization of inflammation. In this study, levels of IL-4, IL-8 and E-selectin were measured in nasal mucosa specimens of intranasal polyposis patients with and without allergic rhinitis, and healthy controls. Healthy controls had significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
1
15
1
Order By: Relevance
“…IL-6 has a chemotactic effect on eosinophils and IL-8 affects both neutrophils and eosinophils, causing their migration to the site of inflammation 15. According to recent studies, increased levels of IL-6 and IL-8 may participate in the primary pathogenesis of CRS and NP as well as in the recurrent episodes 16,17,18. IL-6 is a multifunctional cytokine implicated in various inflammatory conditions including NP pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 has a chemotactic effect on eosinophils and IL-8 affects both neutrophils and eosinophils, causing their migration to the site of inflammation 15. According to recent studies, increased levels of IL-6 and IL-8 may participate in the primary pathogenesis of CRS and NP as well as in the recurrent episodes 16,17,18. IL-6 is a multifunctional cytokine implicated in various inflammatory conditions including NP pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The chemokine IL-8 has been detected in nasal secretions of patients with AR upon allergen challenge [13] and its concentration showed a significant correlation with the symptom score [14]. Furthermore, IL-8 has been shown to be up-regulated in nasal polyps of AR patients and in the nasal mucosa of patients with polyposis as well as in nasal sinusitis [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In fact we found an irregular and low expression of E-selectin in nasal polyps. Ural et al [34] concluded that it is not entirely justifiable that E-selectin has a role in the pathogenesis of intranasal polyposis.…”
Section: Discussionmentioning
confidence: 99%